Structuring the argument : multidisciplinary research on verb argument structure - Bachrach, Asaf; Roy, Isabelle (Writer on linguistics); Stockall, Linnaea (Language faculty and beyond, 2014)
We investigate so-called causative psych nominalizations (CPNs), i.e., nominalizations of object experiencer (OE) verbs that realize non-agentive causers as external arguments. While they are ruled out in English (Grimshaw 1990; Iwata 1995; Pesetsky 1995) and have been suggested to be cross-linguistically banned (Landau 2010), we show that Romanian and Greek derive CPNs from the subject experiencer (SE) form of alternating OE verbs. We analyze them as nominalizations of the anticausative SE form of these verbs. Our results suggest a structural difference between Romanian/Greek and English psyc.